Dissolution of silicic acid from amosite and quartz dusts under physiological conditions. - Rahman, Q.; Beg, M. U.; Viswanathan, P. N. (Scandinavian Journal of Work, Environment & Health, 1975)
The dissolution of silica from amosite dust in human serum and in Ringer buffer at 37 degrees C was found to be significantly higher than that from quartz. The significance of this finding in relation to their fibrogenic effects has been discussed.
Keywords: amosite; amosite dust; dust; experimental physiology; physiological conditions; quartz; quartz dust; silicic acid; toxicity